1992
DOI: 10.1111/j.1651-2227.1992.tb12098.x
|View full text |Cite
|
Sign up to set email alerts
|

Total leukocyte and neutrophil count changes associated with antenatal betamethasone administration in premature infants

Abstract: The white blood cell counts of 84 premature infants were included in a retrospective study of 45 infants treated antenatally with betamethasone and 39 non-treated infants. A significant increase in neutrophil and immature neutrophil forms was found in the treated group when the drug was administered to the mother close to delivery. This effect lasted for three days. Afterwards, although the counts were not significantly high compared to the control group, their physiological decrease was delayed. This study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
1
4

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 10 publications
2
18
1
4
Order By: Relevance
“…This is consistent with other studies of factors influencing WBC and neutrophil counts. [5][6][7]9 Previous studies of the association between neutrophil count and neonatal outcomes have tended to exclude births following pregnancy complications suspected to affect differential blood counts. 4 Interestingly, associations between low neutrophil count, BPD and IVH in this study that excluded key pregnancy complications and infants exposed to antenatal steroids were similar to ours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with other studies of factors influencing WBC and neutrophil counts. [5][6][7]9 Previous studies of the association between neutrophil count and neonatal outcomes have tended to exclude births following pregnancy complications suspected to affect differential blood counts. 4 Interestingly, associations between low neutrophil count, BPD and IVH in this study that excluded key pregnancy complications and infants exposed to antenatal steroids were similar to ours.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not find race to be a major factor influencing the counts. Antenatal steroids are well known to have a stimulating effect on leukocyte and neutrophil counts 7 by enhancing the release of neutrophil and decreasing their clearance from the circulation. 22 Consistent with this, we found that neutrophil counts were affected by exposure to antenatal steroid therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] Neonatal LR has been described in a number of case reports in association with various clinical conditions including prematurity, chromosomal anomalies, exposure to antenatal corticosteroids (ANS), severe anemia, infections, and bronchopulmonary dysplasia (BPD). 8,9,[13][14][15][16][17][18][19][20] In the recent clinical studies by Calhoun et al 10 and Rastogi et al, 21 LR occurred in 1.3% to 15% of infants admitted to neonatal intensive care units, with no significant association demonstrated between LR and maternal and neonatal variables. In addition, Zanardo et al, 20 in a retrospective case-controlled study of preterm infants with gesta-tional age of Ͻ32 weeks, showed that BPD was associated with higher incidence of LR (5 of 50 vs 0 of 50; P ϭ .001).…”
mentioning
confidence: 99%
“…This mother received antenatal steroids that have been proposed as being associated with leukemoid reactions, however, this possible association has not been confirmed in subsequent case series and mechanistic studies. 6,8,12 Given the initial elevation of the maternal WBC count and the microscopic analysis of the placenta, bacterial chorioamnionitis is a possible cause of the infant's high WBC count; however, all bacterial cultures were negative and there were no toxic granulations or vacuolization noted on the infant's peripheral blood smear. Chromosomal analysis was performed to rule out the possibility of leukemoid reaction related to mosaic trisomy 21 (result: 46XX).…”
Section: Discussionmentioning
confidence: 99%